Imaging taste responses in the fly brain reveals a functional map of taste category and behavior. - Marella, S.; Fischler, W.; Kong, P.; Asgarian, S.; Rueckert, E.; Scott, K. (Neuron, 2006)
The sense of taste allows animals to distinguish nutritious and toxic substances and elicits food acceptance or avoidance behaviors. In Drosophila, taste cells that contain the Gr5a receptor are necessary for acceptance behavior, and cells with the Gr66a receptor are necessary for avoidance. To determine the cellular substrates of taste behaviors, we monitored taste cell activity in vivo with the genetically encoded calcium indicator G-CaMP. These studies reveal that Gr5a cells selectively respond to sugars and Gr66a cells to bitter compounds. Flies are attracted to sugars and avoid bitter substances, suggesting that Gr5a cell activity is sufficient to mediate acceptance behavior and that Gr66a cell activation mediates avoidance. As a direct test of this hypothesis, we inducibly activated different taste neurons by expression of an exogenous ligand-gated ion channel and found that cellular activity is sufficient to drive taste behaviors. These studies demonstrate that taste cells are tuned by taste category and are hardwired to taste behaviors.